Long-term safety and outcome of intravenous treprostinil via an implanted pump in pulmonary hypertension - Richter, Manuel Jonas; Harutyunova, Satenik; Grünig, Ekkehard (The journal of heart and lung transplantation, 2018)
BACKGROUND - We examined safety and long-term outcomes of intravenous treprostinil administered via the implantable LENUS Pro pump in patients with severe pulmonary hypertension (PH). - METHODS - Patients with PH undergoing pump implantation between December 2009 and October 2016 in German referral centers were retrospectively analyzed (end of follow-up: May 2017). The primary objective was to determine long-term safety of the implantable pump. Secondary end points were 3-year survival and prognostic relevance of pre-implantation hemodynamics. - RESULTS - We monitored 129 patients (120 with pulmonary arterial hypertension, 1 with PH due to lung diseases, and 8 with inoperable chronic thromboembolic PH) for 260 patient-years (median follow-up, 19 months; interquartile range, 11-34 months). There were 82 complications/peri-procedural events in 60 patients; of these, 57 were serious adverse events (0.60 per 1,000 treatment-days), including 2 periprocedural deaths due to right heart failure. The incidence of complications related to the pump, catheter, infection, and pump pocket per 1,000 treatment-days was 0.074, 0.264, 0.032 (3 local infections; no bloodstream infections), and 0.380, respectively. Three-year overall and transplant-free survival were 66.5% and 55.7%, respectively (39 patients died; 16 underwent lung transplantation). Baseline cardiac index independently predicted transplant-free survival (multivariate hazard ratio, 1.90; 95% confidence interval, 1.11-3.28; p=0.019; n=95). - CONCLUSIONS - Our data suggest that intravenous treprostinil via the LENUS Pro pump in advanced PH is associated with a very low risk of bloodstream infections, but other serious adverse events may occur. Therefore, this therapy needs standardization and should be offered in specialized PH centers only. Further technical advances of the pump system and prospective studies are needed.
Gesehen am 04.02.2020